The balanced view of the value of conscience - McConnell, D; Savulescu, J (Wiley, 2023)
On the mainstream view, consciences are valuable because they promote moral unity. However, conscience, so defined, will systematically prevent moral growth that threatens unity, even when unity has formed around oppressive moral values. This motivates Carolyn McLeod's alternative ‘Dynamic View’ whereby consciences are valuable to the extent that they are dynamic. Consciences are dynamic when they interact with our best moral judgements to shape or ‘retool’ the moral values underpinning conscience, sometimes at an initial cost to unity. We modify and extend McLeod's account in two ways: (1) We object to her claim that conscience encourages its own retooling. We argue that the opposite is true – conscience creates a motivational barrier to change that moral judgement must overcome to successfully retool conscience. The task of ensuring dynamism, therefore, falls to moral judgement. (2) However, this motivational barrier enables conscience to play a valuable role that McLeod overlooks – compensating for the limitations of moral judgement. On our Balanced View, the value of conscience depends on it being sufficiently open to being shaped by our best moral judgements but inert enough to compensate for distorted moral judgements and to guide action when under cognitive load.